Handbook of Green Chemistry 2010
DOI: 10.1002/9783527628698.hgc026
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Hydrolysis of Nitriles

Abstract: The function, uses and commercial applications of nitrile biocatalysts are reviewed. Particular consideration is given to benefits of the technology regarding the impact of nitrile hydrolysis on the environment. The challenges, solutions and opportunities facing the broader application of this technology are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…On the same year, Hook and Robinson demonstrated that a similar mechanism was also responsible for the ricinine hydrolysis through the ricinine nitrilase [28]. The proposed mechanism has been widely accepted by researchers to date (Figure  3) [13,98,99]. However, recent studies demonstrated that amide compounds might also be formed in the course of nitrile hydrolysis by nitrilase.…”
Section: Introductionmentioning
confidence: 99%
“…On the same year, Hook and Robinson demonstrated that a similar mechanism was also responsible for the ricinine hydrolysis through the ricinine nitrilase [28]. The proposed mechanism has been widely accepted by researchers to date (Figure  3) [13,98,99]. However, recent studies demonstrated that amide compounds might also be formed in the course of nitrile hydrolysis by nitrilase.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococci have been shown to have a variety of important enzyme activities in the field of biodegradation (for reviews see [6] and [7]). These activities could also be harnessed for synthesis of various industrially relevant compounds [8]. One of the most interesting qualities of rhodococci that make them suitable for use in industrial biotechnology is their outer cell wall [9].…”
Section: Introductionmentioning
confidence: 99%